Extraordinary justice : law, politics, and the Khmer Rouge tribunals - Etcheson, Craig, 1955- (Columbia University Press, 2020)
Craig Etcheson, one of the world's foremost experts on the Cambodian genocide and its aftermath, draws on decades of experience to trace the evolution of transitional justice in the country from the late 1970s to the present. He considers how war crimes tribunals come into existence, how they operate and unfold, and what happens in their wake.